From guardianship at origin to the fact guard in destination: recognition of the unknown institution. A purpose of Order Nº 209/2020 (In procedure of exequátur) of the Court of First Instance Nº 6 of San Sebastián - Álvarez Agoués, Laura (CUADERNOS DE DERECHO TRANSNACIONAL, 2020)
The order of the Court of First Instance nº6 of Donostia / San Sebastián of February 19, 2020 (Exequatur 1406/2019), validates the demand of exequatur for the recognition of foreign judicial resolution coming from the courts of Uganda by which it was originally agrees the constitution of the guardianship of a minor in favor of the plaintiffs, of Spanish nationality and residence. In this case, the Court, in application of art. 44.4 of the “Law on international legal cooperation in civil matters” ( LCJIMC) is in favor of recognizing an institution unknown to our legal system, such as coexistence between guardianship and parental authority, and in its qualification work it considers that guardianship is in fact the institution of our legal system to the that the now recognized foreign resolution is adapted for not contravening the Spanish public order.